Long-term dynamics of mind wandering: ultradian rhythms in thought generation. Issue 1 (8th June 2019) - Nakatani, Chie; Ganschow, Benjamin; van Leeuwen, Cees
Abstract: Using the method of experience sampling, we studied the fluctuations in thought generation and cognitive control strength during the wakeful hours of the day, centered around episodes of mind wandering. Thought generation, measured in terms of the number of thoughts that concurrently occupy the mind at sampling time, goes through regular 4–6 h cycles, suggesting the mind operates with an alternation of focused and multitasking modes. Cognitive control strength rises and falls in relative coordination with thought generation, implying that both are occasionally misaligned. This happens, in particular, when cognitive control suddenly drops after having been keeping up with a cycle of thought generation. When this drop occurs while the thought generation cycle is still up, mind wandering appears. As cognitive control quickly resumes before returning to intermediate values, the thought generation cycle begins to fall again, and the mind wandering episode comes to an end. Implications regarding the role of long-term regulation in mind-wandering processes are discussed.